Plant Diversity and Distribution Patterns of Populus pruinosa Schrenk (Salicaceae) Floodplain Forests in Kazakhstan - Liliya Dimeyeva; Anastassiya Islamgulova; Valeriya Permitina; Kapar Ussen; Aleksandr Kerdyashkin; Natalya Tsychuyeva; Zhuldyz Salmukhanbetova; Alfiya Kurmantayeva; Rashid Iskakov; Azhar Imanalinova; Bedel Kaliyev (Diversity, 2023)
Populus pruinosa is listed in the International Union for Conservation of Nature (IUCN) Red List of Threatened Species and the Red Data Book of Kazakhstan. The habitats of the species are associated with the floodplains of desert rivers, including the Syr Darya and the Ili. The reduction in tugai forests is associated with changes in the hydrological regimes of rivers, the reduction in groundwater, fires, and grazing. The aim of this research is to advance our knowledge of the woodlands and forests of P. pruinosa in Kazakhstan by analyzing the cenoflora and forestry characteristics, conducting ecological niche modeling to select suitable habitats for ecological restoration, and identifying rehabilitation strategies. The vegetation was studied using traditional methods of geobotanic field research in 2021 and 2022. Ecological niche modeling includes the calculation of all the environmental variables that are significant for the species, taken in their optimal ranges, and identifying the intersection of all the favorable conditions. To identify these variables, geographically linked meeting points of the studied species, climatic and soil conditions, relief characteristics identified by the SRTM and raster sets of the environmental variables (WorldClim), and distances to watercourses and settlements were accepted for consideration. A total of 102 environmental variables were used.